Peran Partai Keadilan Sejahtera Pada Pelaksanaan Pendidikan Politik Masyarakat Muslim Kota Padangsidimpuan - Afriansyah, Arie; Hasiah, Hasiah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This article discusses the review of siyasa fiqh in political education among Muslims in the city of Padangsidimpuan. This research is field research using a qualitative approach, the primary data source comes from the primary data sourced from the Leaders, secretaries of the Prosperous Justice Party (PKS), and community leaders. Secondary data obtained from laws, books, literature and other data. While the data comes from research results, the Legal Dictionary, the Big Indonesian Dictionary, articles on the internet and other materials that are scientific in nature related to the issues to be discussed in this study. Data collection techniques in the form of Observation, Interview and Documentation. While the descriptive data analysis technique. The results showed that the role of the Prosperous Justice Party in the implementation of political education among the people of Padangsidimpuan city. The party has carried out political education, namely by recruiting party cadres, weekly reviews with PKS cadres (trained), in addition to weekly studies, and writing articles on social networks. Obstacles to the Party in carrying out political education are the negative views of society towards political parties, the tendency of people to be less willing or against politics, political parties are seen as prioritizing the interests of the party. efforts made to overcome obstacles in carrying out political education in the city of Padangsidimpuan, trying to increase public trust in political parties while maintaining the good image of the party, Conducting political education to people who have a tendency of high political interest